Biomassa arbórea nas florestas alagadas ao longo do Rio Branco, Roraima - Farias, Hugo Leonardo Sousa (2014)
Amazonian forests are an important above and belowground carbon reservoir. They play an important role in both the sequestration of atmospheric carbon and storage of carbon as biomass. The aim of this study was to quantify the spatial variation of above ground tree live biomass and evaluate the effects of climatic and environmental predictors along ~400km of flooded forests in the middle and lower rio Branco (Roraima). Specifically, I related plot-based biomass estimates with (i) duration of flooding, (ii) length of the dry season, and (iii) texture and fertility of the soil. A total of 2.432 individuals with diameter at breast height (DBH) ≥ 10 cm where sampled in 54 long (250 meters) and narrow (4 meters) plots of 0.1 hectare. For each individual sampled, were also determined: total tree height and wood density. The above ground live biomass of trees was estimated by the average of three allometric models that consider DBH, wood density, and tree height. Palm biomass was estimated based on a single model that considers only the height of individuals. Biomass estimates presented a 10-fold variation, ranging from 21.5 to 245.15 Mg/ha. No relationship between biomass and climatic variables (mean annual rainfall and length of dry season) were observed. Environmental variables: soil (% clay) and the duration of the flood also did not explain the variation in tree biomass in the flooded forests of the rio Branco. These represent the first tree biomass estimates for the flooded forests of the rio Branco, and the large biomass variation observed in the plots suggest that local stochastic events, forest structure and floristic composition may be more important in explaining biomass variation than climatic and soil factors.